Strategi Pengembangan Komoditas Unggulan di Kelurahan Banturung Kecamatan Bukit Batu Kota Palangka Raya - Andreas Jongguran Sihombing; Evi Feronika Elbaar; Soaloon Sinaga (Journal of Environment and Management, 2020)
Banturung village, located in Bukit Batu Subdistrict, Palangka Raya city, is known with its considerable agricultural products, especially in horticultural crops subsector. The superior horticultural crops commodities, however, needs more attention since input side of production process is still experiencing problems for further development. Hence formulating strategy for its development is a nessecity. This study aims to identify leading commodities and to formulate development strategy for such commodity in the village. A LQ analysis and farmers' preferences were used to determine the superior crops, while SWOT analysis was applied to formulete development strategy for the superior one. The results showed top four commodity were beans (LQ = 8.26), long beans (LQ = 2.75), onions red (LQ = 2.06), and eggplant (LQ = 1.84). The strategies could be took for their development are: 1) increasing cooperation/partnership between farmer institutions and private or government parties, 2) increasing the carrying capacity of infra-structure and facilities, 3) optimizing capital assistance from government as stimulant for processing innovation, mar-keting, and dissemination of products, and 4) providing information and data to support marketing inquiry.